Rancang Bangun Sistem Berbasis Web untuk Konversi Data Excel ke Database MySQL - Ananda Fahira Pasha; Farizi Ilham; Leo Alansyah (CV. Shofanah Media Berkah, 2026)
The rapid development of information technology encourages educational institutions to improve data management effectiveness. SD Islam Plus Al Ijtihad 2 still uses Excel files or spreadsheets as the primary medium for administrative data storage. Long-term spreadsheet usage causes several problems, including data duplication, input errors, and difficulties in integrating data into database systems. This study aims to design and develop a web-based system capable of converting Excel data into a MySQL database automatically and systematically. The research methods include observation, interviews, literature review, system requirements analysis, Unified Modeling Language (UML) design, and implementation using PHP Native and MySQL. The developed system provides features such as Excel file upload, data validation, data transformation, column mapping, automatic import processes, and PDF report generation. The results indicate that the system successfully accelerates data integration, reduces input errors, improves data consistency, and facilitates administrative data management. The implementation of this system is expected to enhance administrative efficiency and support faster and more accurate decision-making processes.